1848 Pa. Laws 182, No. 147, § 13 - (:unkn) unknown (My University, 1848)
. and if any person shall be guilty of carrying any lighted cigar . . . or who shall discharge any pistol or gun, or any fire arms on or near said bridge, so that the said bridge, by possibility, be set on fire, or injured by said cause, he or she so offending shall forfeit and pay to the said corporation, the sum of five dollars for every such offence. . .
Keywords: DISCHARGE